O ensino de competências no Brasil : o que dizem as teses e dissertações no período de 2015 a 2019 - Silva, Diocélia Moura da (2021)
The present research aims to identify and analyze the notion of education by competencies in the Education postgraduate programs in Brazil from 2015 to 2019. Through the CAPES database, the aim was to understand the current stage of discussions on competency-based education in Brazil and the consequences of this model for basic education. The study focused on answering the following question: what do the theses and dissertations of the postgraduate programs in Education (PPGEDU) say about competencies in basic education in the period from 2015 to 2019? We adopted the pluralist theoretical framework supported by the studies of Laval (2004; 2016; 2019; 2020), Dardot and Laval (2016a; 2016b), Nussbaum (2015; 2012; 2005, 2009), Masschelein and Simons (2014), Sacristán (2011) and Silva (2003; 2015; 2018). The method used is analytic-hermeneutic. It is basic qualitative and quantitative research, descriptive-analytical, and with a meta-research character. The data collection procedure was carried out through the search and analysis of theses and dissertations available in the CAPES database, which resulted in a sample of 29 academic works distributed among theses and dissertations. Data were collected and organized into tables and classified according to the linkage of the research (a) to basic education and (b) to high school, elementary school, and early childhood education specifically. Subsequently, the data were organized concerning competency-based education and the object of research; critical or non-critical positioning concerning competency education; theoretical-conceptual affiliation; and the objectives of competency-based teaching. The results showed that the political-pedagogical positioning of theses and dissertations is explained in two antagonistic conceptions, with different stages of discussion, which vary from incipient to a reasonable basis for competency-based education. The first conception sees competency-based education as a formative setback for being allied with conductivism and neoliberalism, arguing that is in line with the critique of education through competencies in basic education. The second conception is that education through competencies is linked to constructivist ideas, standing out as a promise of formative advancement. Greater representation of the works shows that competency-based education does not surpass the conductivist and neoliberal matrix. Therefore, the ideals of competency-based education are contradictory and the promise of formative progress, questionable. Thus, the consequence of adopting competency-based education in basic education is the neglect of comprehensive human training, in favor of fragile technical and instrumental training. The challenge is the debate and deeper analysis of ongoing educational policies anchored in competency-based education, such as the National Common Curriculum Base, as they are based on a naive view of competency-based education in basic education.